Evaluation of the citizenship evidence-based probation supervision program using a stepped wedge cluster randomized controlled trial - Pearson, Dominic A. S. (Crime & delinquency, 2016)
This study evaluated a Risk-Need-Responsivity (RNR) evidence-based offender supervision program, Citizenship, using a randomized controlled trial (RCT). Citizenship has a cognitive-behavioral basis and focuses on education, increasing motivation to change, and community integration. The RCT is a stepped wedge cluster randomized design that has rarely been used in criminal justice and overcomes some ethical objections to RCT implementation. Participants were all medium- and high-risk offenders commencing probation supervision (N = 1,091) in any one of the six office units during the 1-year rollout of the program. Overall, there was a non-significant 20% effect of Citizenship in reducing reconvictions. However, controlling for risk, the hazard with higher risk offenders was 34% lower than for the control group. Results therefore support RNR-based probation supervision.